Puzzle: Day at the zoo. - Dowdle, Eric.
The zoo appeals to the kid in all of us! Our fascination with animals reminds us of how connected we are. In this delightful painting, everyone$1 (Bs out of the cage and having a great time at City Zoo. Look for a lot of monkey shenanigans, and you$1 (Bll laugh when you see what the bears are up to.s
Day at the zoo.
Keywords: jigsaw puzzle